Life Cycle Assessment of the Traditional Earthen Ware Pot: A Comparative Study Of Mpraeso and Vume in the Eastern and Volta Regions Respectively of Ghana. - Kusimi, B.A. (University of Ghana, 2019)
The traditional production of earthenware bowls in Ghana, as any other production activity, generates environmental and health issues over its production cycle. Over the years, little attention has been paid to the impacts related to earthenware production and use in the country. A common and useful tool in evaluating the environmental impacts of a product and promote its sustainability is the Life Cycle Assessment (LCA) tool. This thesis presents a comparative study of the life cycle of traditional earthenware pots produced in Mpraeso and Vume, in Ghana. The LCA methodology employed considered the International Organization for Standardization (ISO) 14040 rules and data from the potters on the production cycle. The unit of analysis was 1kg of the product and the scope of the study was from cradle to grave to examine the stages of the earthenware pot, a commonly used product in Ghana. At the production stage of the cycle, several analyses were carried out on raw materials. Plasticity of raw materials including raw clays, mixed clays and clay additives were performed according to ASTM D4318-05 methodology to ascertain the plastic limit of the substances. Mineralogical analyses of raw materials and pots were ascertained by Scanning Electron Microscopy (SEM). Physio-chemical properties of the clay were also studied, likewise, heavy metals were measured using the Atomic Absorption Spectrometer (AAS). Possible leaching of heavy metals from pots into food through the processes of grinding, serving and storage of food at different temperatures at the use stage were also examined. Further, the human health risk impact of the production and usage of earthenware pots were assessed employing the USEPA health risk and the cancer risk models. Additionally, the pottery socio – cultural issues and perception on production methods and environmental impacts of the industry among the 2 communities were verified through the administration of questionnaire to the potters. The data was analyzed by Principal Component Analysis, Pearson coefficient of correlation and Analysis of Variance. Clay mineralogical and chemical composition showed that the clays of Mpraeso and Vume are composed mainly of Si, Al, Fe, smectite (montmorillonite), kaolinite, illite and quartz as major minerals, and the plasticity of the clays increases with the addition of a temper. There were gender and socio-cultural systems governing the pottery industry in the study areas. Indigenes were not happy with the mass destruction of the environment coupled with no plan of reclamation. Leaching and health risks analyses indicated that, food consumption and storage in unglazed pots is associated with metals of Fe, Co and Ni which were found to be above WHO/FAO recommended levels. More so, human contact during processing and inhalation during extraction over a long period could affect indigenes health. Further assessment of the environmental impact by ReCipe endpoint method in Simapro 7.1 software during the stages of extraction and firing using the traditional methods of production showed intense devastation. The results also demonstrated that energy used in the industry was the major contributor towards resource depletion, environmental and health impacts in the industry. There is the need therefore, for the regularization of the industry by National Board for Small Scale Industry, Environmental Protection Agency, Environment and Sanitation office for health, safety and environmental protection since there are some socio-economic and environmental implications of the pottery production cycle. Regulations and training will also ensure economic benefits to local assemblies and national government through taxation and foreign exchange earnings.
PhD. Environmental Science
Keywords: Earthenware bowls; Ghana; Life Cycle Assessment; Earthenware production; Production cycle